The mechanism and effects of cyanobacterial toxins on human organisms - Pietraszkiewicz, Magdalena; Ślęzak, Andrzej (Polish Journal of Public Health, 2010)
In the last decades an increase in Earth’s global temperature has been observed, which caused favourable conditions for cyanobacterial colonization. The water blooms that are formed by these organisms repeatedly contain a great variety of toxic substances subsumed to secondary metabolites and are hazardous for human’s health and life. Apart from hepatotoxins and dermatotoxins, this group also contains neurotoxins which cause damages to the brain and the nervous system. Among cyanobacterial neurotoxins we can distinguish anatoxin, β-N-methylamino-L-alanine (BMAA), paralytic shellfish toxins (saxitoxin and its isomers), antillatoxins, jamaicamides and kalkitoxin. As a result of the surface contact or penetration into the organism, these compounds may result in skin irritation, allergic reactions, muscle tremor or even death of an organism. Therefore, cyanobacteria may pose a severe medical problem on a global scale that creates new tasks for public health. In this review, the chemical structure, synthesis, properties and mechanisms of action are described. Due to high risk related to contact with cyanobacterial neurotoxins, medical symptoms are also described.